Effects of polyester microplastics and naproxen on lettuce growth and development and soil abiotic factors - Andy Chen; Pamela Jane Victoria A. Barroso; Jennifer Tran; Ashley K. Gance; Miranda A. Kearney (Agrosystems, Geosciences & Environment)
Abstract Microplastics (MPs), formed from the physical breakdown of larger plastics, have been found across a variety of ecosystems. Much research has been done on the effects of MPs in aquatic ecosystems, but fewer studies have explored their effects in terrestrial environments, particularly in agroecosystems where modern practices contribute strongly to MP soil pollution (e.g., plasticulture, fertilization with contaminated biosolids, and composts). Aquatic pharmaceutical contamination is also considered an emerging pollutant threat. Naproxen, a commonly used drug, has been found in wastewater and natural freshwater bodies globally. Thus, crops may be exposed to multiple pollutants simultaneously through soil and water inputs. Our research provides insight into the individual and interactive effects of soil MP pollution intensity and exposure to naproxen‐contaminated water on growth and development of Lactuca sativa (lettuce). Soil abiotic factors (pH, electrical conductivity, and rates of soil moisture loss) are also reported. We found that 7% polyester MP‐contaminated soil significantly reduced total aboveground biomass and coarse root biomass, while both 0.03% and 7% polyester MP‐contaminated soil significantly reduced leaf count and average leaf size. However, 1 mg/L naproxen had no effect on plant growth or development, and there were no interactive effects of naproxen with MPs. MPs also significantly increased rates of soil moisture loss, but we found no effects of MPs or naproxen on soil pH or electrical conductivity. Predicted global increases in soil MP contamination levels will potentially have negative consequences for food systems.